2022
DOI: 10.3390/f13091485
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Precipitation Reduction Slows Down Litter Decomposition but Exhibits Weak to No Effect on Soil Organic Carbon and Nitrogen Stocks in Three Mediterranean Forests of Southern France

Abstract: Forest ecosystems are some of the largest carbon (C) reservoirs on earth. Pinus halepensis Mill., Quercus ilex L. and Quercus pubescens Willd. represent the dominant tree cover in the Mediterranean forests of southern France. However, their contributions to the French and global forest C and nitrogen (N) stocks are frequently overlooked and inaccurately quantified and little is known about to what extent the ongoing climate change can alter these stocks. We quantified the soil organic C (SOC) and N (SN) stocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…On average, P. halepensis , Q. ilex , and Q. pubescens lost 42%, 50%, and 52% of initial litter mass after 2 years of field exposure, respectively. These rates of litter decomposition are similar to those reported in other studies from Mediterranean forested ecosystems [ 36 , 40 , 70 ]. It was reported that around 50% of the mass was lost for Q. pubescens after 25 months of field exposure [ 71 ].…”
Section: Discussionsupporting
confidence: 90%
“…On average, P. halepensis , Q. ilex , and Q. pubescens lost 42%, 50%, and 52% of initial litter mass after 2 years of field exposure, respectively. These rates of litter decomposition are similar to those reported in other studies from Mediterranean forested ecosystems [ 36 , 40 , 70 ]. It was reported that around 50% of the mass was lost for Q. pubescens after 25 months of field exposure [ 71 ].…”
Section: Discussionsupporting
confidence: 90%
“…The results reported above come predominantly from studies of forests under existing climate conditions. To study the dynamics of forest under changed climate, experiments modifying temperature (Rustad et al., 2001), water availability (e.g., Santonja et al., 2022), or atmospheric composition (Norby et al., 2016; United States Department of Energy, 2020) are required. Of these environmental modification experiments, Free‐Air CO 2 Enrichment (FACE) is the most technically difficult for mature forest stands and also tests the most direct physiological connection between forest productivity and the human‐perturbed atmosphere (i.e., changing atmospheric CO 2 as a substrate for photosynthesis and, hence, the terrestrial food web).…”
Section: Carbon Sequestrationmentioning
confidence: 99%
“…Therefore, soils are the largest carbon reservoirs of the terrestrial carbon cycle (Das 2019;Ozlu et al, 2022). The residence or accumulation time of C in the soil is longer than that in vegetation (Santonja et al 2022). The soil holds this large carbon stock and prevents the accumulation of carbon dioxide in the atmosphere, which will increase the problem of climate change (Poeplau et al, 2021).…”
Section: Introductionmentioning
confidence: 99%